International Organizations and the Promotion of Effective Dispute Resolution AIIB Yearbook of International Law 2019 - Quayle, Peter; Gao, Xuan (AIIB Yearbook of International Law, 2019)
This second volume of the AIIB Yearbook of International Law examines a series of overarching themes and relationships regarding the role of international organizations in promoting effective dispute resolution. Readership: All international legal practitioners, academics and students interested in international law, international organizations (including international financial institutions), the Asian Infrastructure Investment Bank generally, and the international legal status and accountability of multilateral institutions, together with international dispute resolution.